Spesial Produk, Citra Merk, Konformitas dan Perilaku Merokok - Nelwan, Vecky (Persona:Jurnal Psikologi Indonesia, 2015)
Abstract. The objective of the research was to examine whether there is a specialrelationship existed between product ,brand image and conformity to smoking behavior.The subjects of research was 84 smokers in Karangbesuki village Sukun District,Malang City who selected randomly, with the characteristic of cigarette smoker mustconsume 1 (one) pack of cigarette a day and 25 to 60 years old. Data collection wasusing a psychological scale which comprised of smoking behavior scale, productspesialty scale,brand image scale and conformity scale. Data were analyzed withmultiple regression analysis and partial correlation with Computer Program SPSS 2.0.0for Windiows. Result of data analysis indicated that product specialty was positivelycorrelated ,band image and conformity were significantly and simultaneously correlatedwith smoking behavior. In partial manner, product spesialty was positively correlatedwith smoking behavior and there is positive relationship between brand image andsmoking behavior. Conformity and smoking behavior has particularly positiverelationship. The contribution of the influence of variabels of product specialty,brandimage and conformity to smoking behavior was 64,1 %.Keywords : Smoking behaviors, Product special, Brand image, Conformity